(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
The stem bark of crude methanolic extract of Milletia chrysophylla and it fractions were screened for phytochemical constituents and antimicrobial activity against Methicillin resistant Staphylococcus aureus, Staphylococcus aureus, Streptococcus pyogenes, Corynebacterium ulcerans, Escherichia coli, Neisseria gonorrhoae, Salmonella typhi, Shigella dysenteriae, Proteus vulgaris, Candida albicans, Candida krusei and Candida tropicalis using the ager-well diffusion method. The analysis showed relevant and interesting activities for all the extracts on most of the organisms. However, their sensitivities were a bit lower relative to the positive control. Zones of inhibition ranged between 20 - 31 mm for all the extracts and their MIC values were between 0.06 -2.5 mg/ml with the n hexane and chloroform fractions having the least values for some of the organisms. Similarly, the MBC/MFC values recorded ranged between 0.13 - 10 mg/ml with the chloroform fraction, also having the least value of 0.13 mg/ml for Escherichia coli, Shigella dysenteriae and Candida albicans which indicates a possible higher concentrations of the active components therein. Phytochemical studies of the crude extract, showed presence of carbohydrates, glycosides, cardiac glycoside, saponins, tannins, condensed tannins, flavonoids, alkaloids, steroids and triterpenes. The presence of these metabolites and the inhibitory effect of each of the extracts on most of the test pathogens showed the broad spectrum antimicrobial activities of the plant and justify it use in ethno medicine for treating ailments of microbial origin thus, introducing the plant as a candidate for new drug search and development for ailments due to these pathogens.